Between words and things: nominalism and conceptualization in the historiography of ideas and the affirmation of the “Escola do Recife”: nominalism and conceptualization in the historiography of ideas and the affirmation of the “Escola do Recife” (Revista de História da UEG (REVHIST), 2021)
The work seeks to discuss the problem of names and concepts within a broad historiographic framework that includes several debates and authors in multiple temporal and spatial contexts, but which revolve around the so-called “History of Ideas”, “Intellectual History” and “History of intellectuals”. We propose to analyze the ways in which names and concepts, sometimes, constitute the same epistemological weave that gives meaning to historiographical narratives and how, sometimes, they determine the conceptions of history, time, document and narrative for these authors and works. For that, we resort to the constitution of the so-called “Escola do Recife” as a concept referring to a group of intellectuals and their effort to establish an intellectual movement born in the Empire, but which unfolds throughout the republican period. Thus, we intend to contribute to the criticism of the theory of History and historiography in its epistemological dimension, in addition to the clash between narrativism and meta-history.Keywords: Nominalism. Conceptualization. Historiography. History of Ideas.